Density profiles of Ar adsorbed in slits of C O2: Spontaneous symmetry breaking revisited - Szybisz, L. (2008)
A recently reported symmetry breaking of density profiles of fluid argon confined by two parallel solid walls of carbon dioxide is studied. The calculations are performed in the framework of a nonlocal density functional theory. It is shown that the existence of such asymmetrical solutions is restricted to a special choice for the adsorption potential, where the attraction of the solid-fluid interaction is reduced by the introduction of a hard-wall repulsion. The behavior as a function of the slit's width is also discussed. All the results are placed in the context of the current knowledge on this matter. © 2008 American Institute of Physics.